2005
DOI: 10.1080/08985620500096711
|View full text |Cite
|
Sign up to set email alerts
|

Are Scottish firms meeting the ICT challenge? Results from a National Survey of Enterprise

Abstract: This paper examines the diffusion of Information Communication Technology (ICT) into firms in Scotland and northern England. Data concerning the adoption of micro-computers, e-mail, the Internet, ISDN, in-house website, and the automation of business functions is analysed by industry, firm size, firm age, rate of growth, export involvement, and innovation activity. The results from a sample of 1347 firms found an overall increase in the adoption of ICT in firms between 1998 and 2001. The increase is led by old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Until recently rural businesses have been observed to be slower in terms of ICT adoption than their urban counterparts (Keeble et al, 1992;Buhalis and Main, 1998;Smallbone et al, 2002;Haugh and Robson, 2005). These observations have been identified as surprising by those who have theorised that since rural firms have more to gain from the benefits of the internet in terms of extending reach particularly, they would be more, not less, likely to engage in internet-based business activities than urban firms (Vaessen and Keeble, 1995).…”
Section: The Rural Business Environmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Until recently rural businesses have been observed to be slower in terms of ICT adoption than their urban counterparts (Keeble et al, 1992;Buhalis and Main, 1998;Smallbone et al, 2002;Haugh and Robson, 2005). These observations have been identified as surprising by those who have theorised that since rural firms have more to gain from the benefits of the internet in terms of extending reach particularly, they would be more, not less, likely to engage in internet-based business activities than urban firms (Vaessen and Keeble, 1995).…”
Section: The Rural Business Environmentmentioning
confidence: 89%
“…For example, Haugh and Robson (2005) summarise potential benefits of business internet adoption and Rodgers et al (2002, p.184) claim that it is increasingly required for firm survival: "for all intents and purposes, you cannot compete nowadays without some kind of e-business strategy". For small firms specifically, the democracy afforded by the internet has been theorised as affording greater competitiveness through providing a more level playing field in terms of visibility, profile and market opportunity previously characteristic of large firms with sufficient resources for these (Galloway, 2006).…”
Section: The Internet and Business: Theoretical Considerationsmentioning
confidence: 98%
“…Firms can own a website to develop a wide range of activities from information adoption to business transformation and creation of new business models (Teo and Pian 2004). Evidence shows that a great number of small firms use their own website mainly to obtain information and as a communication tool (Sadowski, Maitland, and Van Dongen 2002), whereas in large firms, electronic transactions are more common (Haugh and Robson 2005).…”
Section: Website Adoption By Firmsmentioning
confidence: 99%
“…Ahmed (1998) pointed out that among the characteristics that distinguish highly innovative firms from less innovative firms is top management commitment financially and emotionally in support of innovation (Meyer & Goes, 1998). Haugh and Robson (2005) found firms that adopted information technology were more likely to have top management committed to the adoption process. In the implementation of intranet systems in firms, Eder and Igbaria (2001) found that management support has a strong influence in the diffusion and infusion of intranet systems in firms.…”
Section: Moderator Variables-management Characteristicsmentioning
confidence: 98%